PROFIL PENGGUNAAN OBAT PADA PASIEN GOUT DAN HIPERURISEMIA DI RSU ANUTAPURA PALU - Nur Fadhilatu Rahmah; Alwiyah Mukaddas; Safarudin Safarudin (Universitas Tadulako, 2016)
Gout is a type of inflammatory arthritis triggered by the crystallization of uric acid within the joints and is often associated with hyperuricemia. Hyperuricemia is a condition with high blood uric acid levels (above normal). This study aimed to describe drug use profile of gout and hyperuricemia inpatients in Anutapura Hospital, Palu. This is a descriptive study of which samples taken retrospectively. The result showed that the characteristic of 32 inpatients are as follows : most (71.86%) of them are male, 71.86% aged 18-59 years old, 21.86% had high school educational degree, and 21.86% are civil servants. As many as 32.18% of the patients had pain clinical manifestation, 93.75% were diagnosed with gout and 90.63% had high uric acid levels. Patients with amount variation of 5 to 8 drugs were 78.13% dominated by oral anti-inflamatory class of drug therapy (46.3%), with oral NSAIDs as much as 17.71% such as meloxicam (9.71%). Most patients got tablets (50%) and the drugs were found 71.43% in oral route of administration. Keywords : Gout, Hyperuricemia, Anti-inflamatory, NSAIDs.